再論複製人——一個比較倫理的分析: Liberal and Confucian Perspectives on Human Cloning - CHAN, Jonathan (International Journal of Chinese & Comparative Philosophy of Medicine, 2001)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 本文的主要目的是探討複製人類的行為本身是否合乎道德，即撇開安全性和風險等因素，僅僅考慮有關行為本身是否合乎道德這一問題。本文嘗試從（i）複製的目的以及（ii） 複製人的道德地位兩方面來考察有關問題。與此同時本文亦嘗試從一個比較倫理的視野，主要是從自由主義（強調自由權利）的生命倫理和儒家的生命倫理的道德視域，來分析有關問題。根據本文的分析，上述自由主義的生命倫理和儒家的生命倫理的道德視域對於複製的目的以及複製人的道德地位均有著不同並且是互相衝突的道德立場。 A proper assessment of the moral status of applying the somatic nuclear transfer technique to human involves three important moral questions. The first question is concerned with the safety of using the technique, i.e., whether using the new technology on human in this stage will pose an unacceptable risk to the cloned child. Indeed, one major objection to cloning human beings is that the technique of somatic nuclear transfer may cause harm to the cloned child. For instance, the U.S. National Bioethics Advisory Commission (NBAC), among others, argues against human cloning in this vein. It claims that "current scientific information indicates that this technique is not safe to use in humans at this time," and that "〔at〕 present, the use of this technique to create a child would be a premature experiment that would expose the fetus and the developing child to unacceptable risks" (NBAC 1997, "Executive Summary"). As I have argued elsewhere, (Jonathan Chan, ’Human Cloning, Harm, and Personal Identity,’ in Gerhold K. Becker (ed.), The Moral Status of Persons: Perspectives on Bioethics, Rodopi B. V., Amsterdem/ Atlanta, 2000, pp.l95-207), this harm-based argument is far from conclusive. Firstly, the question of how safe and reliable human cloning might be can only be answered by further scientific investigation, and so far scientists do not have strong evidence to prove that cloning human beings is extremely dangerous. Since the risk in question cannot be accurately determined unless scientists are allowed to carry out scientific research on the effects of applying the cloning technology to humans, it is unfair to urge a ban on human cloning by arguing that the technology is unsafe. Secondly, the argument faces the difficulty of what is sometimes called "the non-identity problem." The argument of the non-identity problem runs as follows: It is impossible for the cloned child to be harmed by the act of human cloning since it is this same act that caused the child to exist. Had the act not been performed, the child would not have existed and, hence, the child would not be better off. It follows, then, that performing the act of human cloning would do no harm to the child. The second important moral question concerning human cloning is the one concerned with the purpose of cloning humans. There are three different types of purposes in relation to human cloning. The first type is the ones that I describe as "purely reproductive." With these purposes, people choose to clone a child simply because they want to have and rear their own child and for nothing else. In this case, the motive of these people is not much different from that of those using artificial reproductive technology such as IVF. The second type is the "non-reproductive" ones. To clone a child, for instance, mainly for the purpose of scientific investigation, without any intention of rearing the child, is a paradigm case of cloning humans for the non-reproductive purpose. The third type is the ones that I describe as "mixed" purposes. A set of purposes is a mixed one if and only if it has both the reproductive and non-reproductive components. To clone a child, for instance, so as to provide a son and heir, or to create a sister for Bill, falls into this category. In the above, I have put forward a scheme that classifies the purposes of cloning humans into three different categories. With this scheme of classification, I hope to clarify some moral issues in the current debates concerning human cloning. It will be argued that the Kantian critique that human cloning makes the cloned child purely a means will not stand with respect to the purely reproductive purpose. For unless we deem all (natural or non-natural) reproductive acts as the ones that make people purely a means, the generalized criticism that human cloning makes the cloned child purely a means does not have a strong ground when it is viewed from the Kantian perspective. To rear a child is to develop a parent-child relation, and to foster this relation is to create a certain good that is internal rather than instrumental. For this reason, it is sensible to treat the act of creating a child with a view to rearing him or her as non-instrumental. However, as to the cases in which a child is cloned without the intention of rearing him or her, the conclusion will be very different. ln these cases, the child is created not for developing a parent-child relation but simply for other purposes, say, for scientific investigation. Then, the application of the Kantian principle to these cases is quite intuitive. The third important question concerning the morality of human cloning is the one concerned with the moral status of the human clone. Some philosophers use the "delayed identical twins" metaphor to describe the relation between the clone and his or her original. It will be argued that the above metaphor is highly misleading. It is misleading because the clone and the original cannot have that kind of relation. Rather, the clone is just the original’s biological extension. One might wonder what moral implications we can draw from this conclusion. It will be argued that the moral implications that we can draw from the above conclusion is relative to our moral perspectives. For those who hold the liberal moral perspective, so far as the clone has self-consciousness and autonomy, his or her moral status is not different from a normal human person. His or her own identity will not be affected by the fact that he or she is just the original’s biological extension. However, for those who hold the Confucian moral perspective, the conclusion will be very different. According to the Confucian moral perspective, one’s own identity is defined in terms of the five basic human relations, particularly, the parent-child relation. As the clone is just his or her original’s biological extension, he or she cannot have the natural parent-child relation with any person. That being the case, the clone will not have a complete identity as a normal person has. Then, to clone a human, even for reproductive purpose, would violate the moral standards of the Confucian moral perspective. DOWNLOAD HISTORY | This article has been downloaded 81 times in Digital Commons before migrating into this platform.